The relationship between personality traits, caring characteristics and abuse tendency among professional caregivers of older people with dementia in long‐term care facilities. Issue 17 (1st July 2020) - Chen, Weichen; Fang, Fan; Chen, Yu; Wang, Jin; Gao, Yuanmin; Xiao, Julan
Abstract: Aims and objectives: To explore the relationship between personality traits, caring characteristics and abuse tendency among professional caregivers of older people with dementia in long‐term care facilities in China. Background: Elder abuse is a serious global health problem and human right violation with high incidence among older people with dementia. There are many investigations about impact factors of risk of abuse among family caregivers of older people with dementia. However, in long‐term care facilities, the situation of abuse tendency needs further investigation. Design: Cross‐sectional study. Methods: An observational survey was conducted according to the STROBE checklist. We investigated 156 professional caregivers of older people with dementia in three long‐term care facilities in Guangzhou, China. Participants completed a demographic questionnaire, the Caregiver Abuse Screen (CASE) and the Neuroticism Extraversion Openness Five‐Factor Inventory (NEO‐FFI). Data were analysed using Mann–Whitney U tests, Kruskal–Wallis tests, Spearman's rank correlation and logistic regression analyses. Results: Over half of the participants (51.9%) reported abuse tendency to the older people with dementia. There was a significant negative correlation between the caregivers' agreeableness scores of NEO‐FFI and their CASE scores. Multivariate logistic regression analyses highlighted that protective factors of abuse tendency were caregivers' agreeableness, care recipients' source of finances and their duration of dementia while higher care difficulty and presence of older people's behavioural and psychological symptoms of dementia (BPSD) were the risk factors. Conclusion: Caregivers' agreeableness personality trait and the caring characteristics of older people with dementia may be relevant to abuse tendency in long‐term care facilities. Further study with a larger sample size is needed to validate such a correlation. Relevance to clinical practice: Older people with dementia are at high risk for abuse. Prospective caregivers could pay more attention to developing their own agreeableness. The managers might establish monitoring system for reducing the abuse.